2023
DOI: 10.3390/ma16020879
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Investigation on the Flexural Behaviour of Prestressed NC-UHPC Composite Beams

Abstract: To investigate the normal section strength and cracking bending moment of normal concrete–ultra-high-performance concrete (NC-UHPC) composite beams, calculation formulas were established considering the tensile strength of UHPC based on the current railway bridge design code. Using the railway T-beam as a template, prestressed NC-UHPC composite beams with different NC layer heights were built. A static bending test was performed, the pressure of the steel strand and the deflection and strain of the beam were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The UHPC-NC composite beam was developed to reduce the high initial cost of materials, which influences the application of UHPC in structures. In addition, a higher load-carrying capacity and increased cracking resistance are expected for the UHPC-NC composite beam compared with RC beams [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The UHPC-NC composite beam was developed to reduce the high initial cost of materials, which influences the application of UHPC in structures. In addition, a higher load-carrying capacity and increased cracking resistance are expected for the UHPC-NC composite beam compared with RC beams [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is difficult to precisely control the properties of concrete, a gradient structure can also enhance the macro-performances with different components and mix proportions [ 28 , 29 , 30 , 31 ]. Several investigations have reported on UHPC-NC combined structures [ 32 , 33 , 34 , 35 , 36 ]. Zhang et al [ 37 ] studied the NC-UHPC composite members in continuous box-girder bridges.…”
Section: Introductionmentioning
confidence: 99%
“…Here, two 2200 mm long NC-UHPC composite columns consisting of UHPC and NC columns were experimentally tested, and the results showed that the creep coefficients of the NC-UHPC significantly decreased compared with NC beams. Lin et al [ 34 ] explored the bending performance and cracks of railway T-beams composited with UHPC and NC. Three slab specimens with a cross-section of 300 × 600 mm and a height of 650 mm were prepared using UHPC and NC composites, and it was found that the strength and cracking moment was reduced in the composite structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation